2007
DOI: 10.1002/ijc.22796
|View full text |Cite
|
Sign up to set email alerts
|

Individual and joint use of statins and low‐dose aspirin and risk of colorectal cancer: A population‐based case–control study

Abstract: Recent research has drawn attention to protective effects of statins on colorectal cancer (CRC) and possible joint effects with other drugs. Because statins are often administered in combination with low-dose aspirin for the prevention of cardiovascular disease, the aim of our study was to investigate individual and combined effects of statins and low-dose aspirin on CRC risk. We assessed use of statins and low-dose aspirin in 540 cases with histologically confirmed incident CRC and 614 control subjects in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…Cohort subjects were followed for a primary diagnosis of CRC from enrollment until the earliest of the following events: date of diagnosis of cancer (except non-melanoma skin cancer), date of death, date of emigration, or 30 [43].…”
Section: Ascertainment Of Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort subjects were followed for a primary diagnosis of CRC from enrollment until the earliest of the following events: date of diagnosis of cancer (except non-melanoma skin cancer), date of death, date of emigration, or 30 [43].…”
Section: Ascertainment Of Crcmentioning
confidence: 99%
“…A recent post-trial analysis has suggested that the chemopreventive effect of NSAIDs on colorectal neoplasia may vary by body mass index (BMI) as marker for obesity [27]; however, the epidemiologic data on the influence of BMI are conflicting [19,21]. There is also some evidence that the chemopreventive effect of NSAIDs may be increased by use of statins [28][29][30][31], although the cumulative epidemiologic evidence to date does not point to a material reduction in CRC risk with statin use [32].…”
Section: Introductionmentioning
confidence: 99%
“…51 In a population-based case-control study, the effects of statins and aspirin were evaluated on the risk of colorectal cancer. 52 Overall, 537 patients with histologically confirmed incident colorectal cancer and 612 control individuals were included in the study. Regular use of low-dose aspirin (94% of doses used were 100 mg) was associated with modest risk reduction on colorectal cancer (adjusted OR 5 0.77, 95% CI 5 0.55-1.07), while a stronger risk reduction was found associated with regular use of statins, mostly atorvastatin and simvastatin (OR 5 0.65, 95% CI 5 0.43-0.99).…”
Section: Cancer Chemoprevention By the Combinations Of Statins And Nsmentioning
confidence: 99%
“…With the exception of the latter two variables, these factors too have been documented by other researchers to be associated with neoplasms in the large intestine. [21][22][23][24][25][26][27][28][29] What was unique to this particular study was the identification of potentially two new risk factors for proximal neoplasms within the asymptomatic screening population (use of estrogen and a history of cancer other than CRC). Although it would have been both provocative and insightful to be able to compare and contrast the outcomes of this investigation with the outcomes of others mentioned in this article, this was not realistically feasible because of diverse study designs, inclusion and exclusion criteria, operational definitions for the distal colon, applications of multivariate and statistical techniques, sample sizes, baseline demographic characteristics, and control or reference groups.…”
Section: Discussionmentioning
confidence: 99%